EFFECT OF ULTRASOUND ACTIVATION OF SHS-CHARGE ON THE FINAL PRODUCT - V. V. Klubovich; M. M. Kulak; V. I. Marusich; V. G. Samoletov; E. V. Khruschev (Литьë и металлургия, 2016)
The paper describes the effect of ultrasound activation of dolomite, which is used for producing refractory material by the SHS method, on the final product. X-ray investigation has demonstrated that ultrasound activation of the initial charge brings about changes in the phase composition of the synthesized product.